α-Pheromone Precursor Protein Foc4-PP1 Is Essential for the Full Virulence of Fusarium oxysporum f. sp. cubense Tropical Race 4 - Lu Liu; Yinghua Huang; Handa Song; Mei Luo; Zhangyong Dong (Journal of Fungi, 2023)
Fusarium oxysporum f. sp. cubense (Foc), which causes Fusarium wilt of bananas, is considered one of the most destructive fungal pathogens of banana crops worldwide. During infection, Foc secretes many different proteins which promote its colonization of plant tissues. Although F. oxysporum has no sexual cycle, it has been reported to secrete an α-pheromone, which acts as a growth regulator, chemoattractant, and quorum-sensing signaling molecule; and to encode a putative protein with the hallmarks of fungal α-pheromone precursors. In this study, we identified an ortholog of the α-pheromone precursor gene, Foc4-PP1, in Foc tropical race 4 (TR4), and showed that it was necessary for the growth and virulence of Foc TR4. Foc4-PP1 deletion from the Foc TR4 genome resulted in decreased fungal growth, increased sensitivity to oxidative stress and cell-wall-damaging agents, and attenuation of pathogen virulence towards banana plantlets. Subcellular localization analysis revealed that Foc4-PP1 was concentrated in the nuclei and cytoplasm of Nicotiana benthamiana cells, where it could suppress BAX-induced programmed cell death. In conclusion, these findings suggest that Foc4-PP1 contributes to Foc TR4 virulence by promoting hyphal growth and abiotic stress resistance and inhibiting the immune defense responses of host plants.